Bringing context and educational leadership together: fostering the professional development of school principals - Brauckmann, Stefan; Pashiardis, Petros; Ärlestig, Helene (Professional development in education, 2023)
Policy makers increasingly acknowledge that problems and challenges arising at the school level should be resolved on site. At the same time, the political expectation to delegate more responsibility to the individual school is rather heavily contrasted with the weak knowledge about how this new public management approach can be translated into successful leadership practices. Thus, considering that there is a close relationship between context and leadership, principal preparation programmes should be guided by a deeper examination of contextual factors. Against this background, we aim to critically examine existing views of practitioners and researchers on the challenge of establishing more context-sensitive school leadership preparation programmes in an era of New Public Management in Education. In doing so, we introduce the Swedish Model of principal preparation as an example for a more context-sensitive leadership preparation program. To that end, we argue that a differentiated perspective about contextual conditions and their role as facilitators or obstacles to effective leadership must be further explored. Moreover, school leaders should be encouraged to consider the relevance of such approaches to their own needs.